SISTEM KEKERABATAN DALAM KEBUDAYAAN MINANGKABAU: PERSPEKTIF ALIRAN FILSAFAT STRUKTURALISME JEAN CLAUDE LEVI-STRAUSS - Munir, Misnal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2015)
The culture of Minangkabau is one culture that embraces the matrilineal kinship system until now. This article aims to comprehend a kinship relation in the culture of Minangkabau based on the anthropological structuralism theory of Levi-Strauss. The kinship system of the culture of Minangkabau, according to the structuralism perspective of Levi-Strauss, places a man as a medium in communicating among clans or tribes. The matrilineal system of the culture of Minangkabau places a woman as a remaining side, while a man as a visiting side to woman house. The matrilineal system places a woman as a heritant of wealth and a man as a person who move to woman house.